(untitled) - Maragoni, Alejandro G. (New York, 2005)
The first authoritative source on the subject, this reference discusses the various levels of structure that influence the macroscopic physical properties of fat crystal networks. Fat Crystal Networks summarizes 50 years of structural research in the field, as well as a wealth of information on fat crystal networks pertinent to real-world challenges in industry. The book covers the physical chemistry of crystallization, emphasizing structure and mechanical properties as well as crystallization processes, and rheology of crystal networks in fats and lipid systems. Featuring a digital library containing 8000 high-resolution images of crystallized fats including cocoa butter, milkfat, milkfat fractions, and palm oil, the book contains state-of-the-art advancements gleaned from the editor's personal research in the field as well as contributions from several highly regarded colleagues. Fat Crystal Networks illustrates a wide range of analytical methodologies including pioneering studies on the use of 3-dimensional microscopy and the microanalysis of fat crystal networks and an introduction to the use of fractal analysis in the natural sciences. It also highlights recent methods to alter fat functionality through blending and physical manipulation, in-depth research available on the phase behavior of triacylglycerols, and coverage of formulation problems currently affecting the food industry. About the editor… Alejandro G. Marangoni is a Professor and Canada Research Chair at the University of Guelph, Ontario, Canada. He is the author, coauthor, or editor of numerous professional publications, including Physical Properties of Lipids and Soft Materials.
Keywords: Lipids,Crystals; Microstructure,Mathematical models